Costs of Medical Care of MRSA Patients at the End-of-Life in a Geriatric Ward - Adelhardt, Thomas; Hessemer, Stefanie; Docter, Katrin; Sieber, Cornel; Ostgathe, Christoph; Schöffski, Oliver (Gesundheitswesen, 2018)
OBJECTIVE: The present study addresses the financial effects of incidences of MRSA in the geriatric ward of a German hospital on patients receiving end-of-life care. The main cost drivers will be identified and the costs calculated. METHODOLOGY: A retrospective analysis for a period of one year was conducted for the geriatric ward of a German hospital. In addition to the duration of the patient's stay and the total costs of his/her case, individual cost categories such as personnel and material costs were also examined. In order to enable a cost comparison of MRSA-positive and MRSA-negative patients, matching was used. T-tests were used for purposes of comparison with the case groups. FINDINGS: A total of 107 cases were included in the study; in 27 of these cases, MRSA was detected. Patients with MRSA were found to have a longer average stay and to incur higher average costs. There were no statistically significant differences in the duration of hospital stay between MRSA-positive and MRSA-negative patients. Furthermore, no statistically significant differences were seen in the total costs per case. Significantly higher daily personnel costs for nursing staff were observed for MRSA-positive patients in the case group of patients with lower than average total costs. For MRSA-positive patients, these costs amounted to € 97.18, while MRSA-negative patients incurred € 80.44 in costs. Costs of doctors, medical technicians and non-medical personnel and material costs for infrastructure showed an opposite tendency. If the case groups for different total costs are not considered, no significant differences between MRSA-positive and MRSA-negative patients were found for the individual cost categories examined. CONCLUSIONS: Although we demonstrated that MRSA-positive patients had longer stays and caused higher overall costs in the geriatric ward, we did not find any statistically significant differences between MRSA-positive and MRSA-negative patients. One of the main cost drivers in the care of MRSA-positive patients was identified as the daily personnel costs for nursing staff. Analysing processes related to patients' nursing care can be the first step in attempts to make care for MRSA-positive patients more effective and efficient.
EVALuna2:35552